1997
DOI: 10.2105/ajph.87.12.1931
|View full text |Cite
|
Sign up to set email alerts
|

AIDS education in Tanzania: promoting risk reduction among primary school children.

Abstract: OBJECTIVES: The purpose of this study was to test the effects of an education program in Tanzania designed to reduce children's risk of human immunodeficiency virus (HIV) infection and to improve their tolerance of and care for people with acquired immunodeficiency syndrome (AIDS). METHODS: A randomized controlled community trial including baseline and 12-month follow-up surveys was employed. Public primary schools in the Arusha and Kilimanjaro regions of Tanzania were stratified according to location and rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
145
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(151 citation statements)
references
References 12 publications
2
145
0
3
Order By: Relevance
“…Religious affiliation was only reported by three studies, in which the samples comprised a mixture of Catholics, Protestants or Muslims. 64,67,68 Only one study reported whether or not the young people had ever been considered as offenders; 61 in this study, 62% and 57% of the intervention and comparison groups, respectively, had offended. The respective figures for currently being on probation were 53% and 49%.…”
Section: Other Characteristicsmentioning
confidence: 67%
See 4 more Smart Citations
“…Religious affiliation was only reported by three studies, in which the samples comprised a mixture of Catholics, Protestants or Muslims. 64,67,68 Only one study reported whether or not the young people had ever been considered as offenders; 61 in this study, 62% and 57% of the intervention and comparison groups, respectively, had offended. The respective figures for currently being on probation were 53% and 49%.…”
Section: Other Characteristicsmentioning
confidence: 67%
“…62 Twelve of the RCTs were cluster trials, 11 of which randomly allocated schools, with one allocating school districts. Six of the twelve studies did not provide details of the randomisation process, [63][64][65][66][67]69 although it should be noted that Roberto and colleagues 66 only involved two schools. Of the remaining six studies, the process of Zimmerman and colleagues 71 involved pairing clusters, Coyle and colleagues 58 ranked and paired clusters, whilst Coyle and colleagues, 61 Stephenson and colleagues, 50 and Borgia and colleagues 51 had used processes that involved stratifying or matching clusters.…”
Section: Methods Of Randomisationmentioning
confidence: 99%
See 3 more Smart Citations